DETECTION OF TTV ANTIGEN IN PATIENTS WITH HEPATITIS HBV AND HCV (Iraqi Journal of Medical Sciences, 2019)
Background: Several lines of evidence have suggested the presence of new hepatitis agents, in addition to established hepatitis viruses A-E. Torque Teno virus (TTV) was more prevalent in patients with hepatitis, so it was thought to have hepatotropic properties.Objective: To detect TTV Ag in apparently healthy blood donors and patients infected with chronic hepatitis B virus (HBV) or chronic hepatitis C virus (HCV) by enzyme linked immunosorbent assay (ELISA) technique. Also, to find out any possible association between the study population demographic data and TTV status.Methods: This study was conducted from the beginning of November, 2017 to the end of March, 2018. Serum samples were collected from 50 patients who had chronic hepatitis HBV or HCV and attended to Gastroenterology and Hepatology Teaching Hospital. Also, sera were collected from a total 43 healthy blood donors from the Blood Donation Center in Al-Imamein Al-Kadhimein Medical City. The clinical characteristics of both patients and controls such as alanine transaminase (ALT), aspartate transaminase (AST), hepatitis C virus antibody (HCV-Ab), hepatitis B surface antigen (HBsAg) and hepatitis B core antibody (HBcAb) were obtained from hospital records. Serum samples were tested by ELISA technique for detection of TTV Ag.Results: TTV was detected in 89.2% (33 out of 37) of the HBV-positive patients and in 30.8% (4 out of 13) of the HCV-positive patients versus 23.3% of the healthy blood donor (10 out of 43). Results of this study showed that the prevalence of TTV in HBV patients is significantly higher than HCV patients and healthy blood donors. Concerning risk factors, it was found that there was statistically significant relationship between TTV positivity and mean level of ALT but results indicated that the presence of TTV was not associated with AST, sex, age and history of transfusion, surgery and tattooing. Conclusion: TTV may play a role in hepatitis and its presence was associated with biochemical signs of liver disease, and among patients infected with chronic HBV or HCV.Keywords: Torque Teno virus, hepatitis B virus, hepatitis C virus, healthy blood donorsCitation: khudair EA, Al-Shuwaikh AMA, Farhan NM. Detection of TTV antigen in patients with hepatitis HBV and HCV. Iraqi JMS. 2019; 17(1): 43-49. doi: 10.22578/IJMS.17.1.7
Keywords: Torque Teno virus; hepatitis B virus; hepatitis C virus; healthy blood donors